Citra tubuh, Perilaku Diet, dan Kualitas Hidup Remaja Akhir Mahasiswa Fakultas Kedokteran Universitas Riau - Lilly Haslinda; Yanti Ernalia; Sri Wahyuni (Jurnal Ilmu Kedokteran, 2015)
Late adolescence (17-20 years) is when a child has made a career decision in the future. Body image in adolescentsassociated with eating disorders and psychological problems such as depression. Nutritional status is well alignedwith the quality of life of adolescents. This study aims to determine the body image, dietary behavior, and quality oflife in the period of late adolescence students of the Faculty of Medicine, University of Riau. This study was a crosssectionalanalytical study conducted at the end of the 87 teenage students of the Faculty of Medicine, University ofRiau. Selection of the subject of research conducted with total sampling. Measurements made with the body imagequestionnaire silhouettes body image, dietary behavioral data with the questionnaire (eating attitude test) / EAT-26,and the data Quality of Life with WHO-QOL questionnaire. Furthermore, the data presented descriptively. Of the 87respondents there were 25.3% (22) male subjects and 74.7% (65) female subjects. Based on BMI, there are morenutritional status (overweight and obesity) of 27.6%, less nutritional status (underweight) 17.2%. Based on abdominalcircumference there are 25.3% subjects felt obesity there are 51.7% research subjects who felt dissatisfied with herbody image. A total of 36.8% of research subjects perceive their bodies emaciated, 19.5% perceive overweight and1.2% obese perceived body image. A total of 9.2% of the subjects experienced the possibility of eating behaviordisorders. There are 43.7% of research subjects who have less quality of life.